Impulse control and related disorders in Mexican Parkinson's disease patients - Rodríguez-Violante, Mayela; González-Latapi, Paulina; Cervantes-Arriaga, Amin; Camacho-Ordoñez, Azyadeh; Weintraub, Daniel (Parkinsonism & related disorders, 2014)
Impulse control disorders (ICDs) are a relatively recent addition to the behavioral spectrum of PD-related non-motor symptoms. Social and economic factors may play a role on the ICD phenotype of PD patients. The aim of this study is to determine the prevalence and characterize the clinical profile of ICDs in a sample of low-income, low-education PD patients with no social security benefits from a Latin American country. We included 300 consecutive PD patients and 150 control subjects. The presence of ICD and related disorders was assessed using a structured interview. After the interview and neurological evaluation were concluded, all subjects completed the Questionnaire for Impulsive-compulsive Disorders in Parkinson's Disease-Rating Scale (QUIP-RS). Regarding ICDs and related disorders (hobbyism-punding), 25.6% (n = 77) of patients in the PD group and 16.6% (n = 25) in the control group fulfilled criteria for at least one ICD or related disorder (p = 0.032). There was a statistically significant difference in the QUIP-RS mean score between PD and control subjects (5.6 ± 9.7 and 2.7 ± 4.21, p = 0.001). The most common ICD was compulsive eating for both PD (8.6%) and control (2.6%) groups. The results of this study confirm that for this population, symptoms of an ICD are significantly more frequent in PD subjects than in control subjects. Nevertheless, socioeconomic differences may contribute to a lower overall frequency and distinct pattern of ICDs in PD patients compared with what has been reported in other countries. •Frequency of impulse control disorders in Mexican PD patients was assessed.•25.6% of PD patients and 16.6% of the control group had at least one ICD.•The most common ICD was compulsive eating for both PD (8.6%) and controls (2.6%).•Socioeconomic differences may contribute to a lower overall.